ANALISIS FAKTOR PENYEBAB PESERTA DIDIK YANG MEMILIKI KELOMPOK SOSIAL GENG SMA NEGERI RASAU JAYA - Novianti, Sumayroh; Purwanti, Purwanti; Endang, Busri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research was conducted at State Senior High School of 1Rasau Jaya, Kabupaten Kubu Raya. The method used in this study is qualitative research that will describe the results of the analysis of factors causing gang social groups, with the subject of the study of eight students, two teachers BK, eight parents of learners who are included in social groups gangs, three students who outside the social group of gangs. Social groups of gangs studied amounted to eight students of female sex. Instrument or data collection tool used is triangulation namely, obeservasi, interview, and study documentation. The data analysis uses data collection, data reduction, data display, and verifying data. From the results of data analysis has been done that the internal cause of the gang is due to want to seek identity through the gang, as well as external factors derived from family, school, and community environment. The impact on learning achievement has no effect because the learners have a fairly stable value and not a lot of absent alpha. Efforts made by BK Teachers also have good enough and according to procedure in BK.Keywords: causal factors, gang social groups, learners